Utility, Progress, and Technology: Proceedings of the 15th Conference of the International Society for Utilitarian Studies - Schefczyk, Michael; Schmidt-Petri, Christoph (KIT Scientific Publishing, 2021)
This volume collects selected papers delivered at the 15th Conference of the International Society for Utilitarian Studies, which was held at Karlsruhe Institute of Technology in July 2018. It includes papers dealing with the past, present, and future of utilitarianism - the theory that human happiness is the fundamental moral value - as well as on its applications to animal ethics, population ethics, and the future of humanity, among other topics.